Cost/benefit v perinatologii--I. Vseobecné stanovisko západních ekonomů - Stembera, Z (Ceska gynekologie, 1998)
The mutual cost-benefit relationship of any activity is the main principle of the market mechanism where both these variables are expressed in monetary terms. According to western economists this system cannot be applied, or if so only partly, in the sphere of health services because health benefit can be only in exceptional instances expressed in monetary terms. This is why they recommended for evaluation of health care, incl. perinatal care, other economic models where the health benefit is evaluated by saved lives or improvement of the health status. With this aspect in mind the author described five recommended models for the evaluation of alternative procedures and for evaluation of programmes in perinatology. Each of them is supplemented by examples from clinical practice. Most frequently different views are held on the effectivity of costly screening programmes for early detection of threatened foetuses and intensive care of these neonates, i.e. procedures which are the main cause of rising costs of perinatal care. The author discusses reasons for controversial views on contemporary economic problems in perinatology.
Keywords: perinatální péče; Models, Econometric; lidé; hodnota života; Female; Infant, Newborn; Pregnancy; analýza nákladů a výnosů; Perinatal Care; těhotenství; novorozenec; ekonometrické modely; Cost-Benefit Analysis; ženské pohlaví; Value of Life; Humans